(untitled) (International conference on multidisciplinary science, 2025)
Trophoblastic disease is characteristic only of pregnant women of reproductive age and occurs in 0.1-0.25% of all pregnancies. Cystic fibrosis is most often diagnosed among this pathology. According to WHO (2011), on average, there is one cystic fibrosis per 1,000 births, and approximately 2 out of 100,000 women develop chorioncinoma after childbirth and in the same proportion after abortions.